4 - Gender Issues in Human trafficking in Edo State, Nigeria - Clementina O. Osezua (African Sociological Review, 2016)
This study examined the predominance of human trafficking within a social cultural milieu in Nigeria, by taking into account gender issues that have reinforced the phenomenon in the region. The paper relied on primary data generated from an anthropological fieldwork conducted in the affected area. A total of 120 household heads were purposively selected and interviewed in order to capture family dynamics and power relations and women status in contemporary Benin society. In addition four key-informants were interviewed to appreciate the historical and cultural context of the Benin people. Furthermore, eighteen (18) Focus Group Discussions (FGDs) were conducted among males, females and youths with a view to capturing the insiders’ perspective of the perceived gender issues precipitating human trafficking. Findings revealed that the presence of classical patriarchy as shown in high prevalence of polygyny, male- child preference, inheritance and succession systems and highly controlled female sexuality, segregated and unequal access to critical economic resources have continued to heighten the inequality within the social structure in favour of the male child. The paper concluded that efforts targeted towards eradicating existing gender inequality in the region can potentially mitigate the convoluted challenges posed by high human trafficking incidences in the region.